New genera and species of Carventinae from New Caledonia (Hemiptera: Heteroptera: Aradidae) - Heiss, E. (Zootaxa, 2011)
Only a few taxa of Aradidae were described from the Pacific island of New Caledonia to date. Based on recently collected material, 3 new genera (Kanakaptera n. gen., Rugicarventus n. gen., and Paracaraptera n. gen.) and 7 new species (Ka- nakaptera laticeps n. sp., K. montdoa n. sp., K.heimiana n. sp., K. carininota n. sp.; Rugicarventus pygmaeus n. sp.; Paracaraptera schuhiana n. sp., and Nesiaptera picea n. sp.) are described in this paper. All species are illustrated by colour photographs and a key is provided for the species of Kanakaptera n. gen.